Relationship Between Workplace Incivility, Employee Performance And Employee Engagement In Healthcare Institutions - Sakshee Singh; Indra Meghrajani; Garima Vijh; Jain Prabhu Thomas; Sagar Mohite (ACHSM, 2023)
Workplace incivility is a well-known problem that affects every firm and its environment. Employee engagement may result in physical and mental suffering, impacting how well people perform. The study aims to ascertain the relationship between employee engagement, employee performance, and workplace incivility. For this, scales of the investigated variables were used to build a well-structured questionnaire. The survey questionnaire was sent out to workers and employees of Health Care Institutions. There were 212 valid responses in total. SEM, or structural equation modelling, was utilized to establish relationships. The study's findings rejected hypotheses H1 and H2 showing workplace incivility (WPI) has a detrimental effect on employee engagement (EENG) at ( β= - 0.34, P >.05) and employee performance (EP) at (β = -0.27, P >.05). While adopting the hypothesis H3, employee engagement had a favourable impact on the performance of employees at (β = 0.36 P 0.05).